Preparation method of cellulose nanocrystal modified full-bio-based polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions

By using amphiphilic block copolymer modified cellulose nanocrystals as stabilizers, a cellulose nanocrystal modified all-bio-based polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions was prepared, which solved the hydrophilicity, bacterial growth and ultraviolet aging problems of leather materials, and improved the environmental protection and performance of the emulsion.

CN119899566AActive Publication Date: 2025-04-29SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411959382.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing leather materials have microporous structures suitable for bacterial growth, hydrophilicity causes surface hardening and cracking, and ultraviolet rays destroy the collagen structure, leading to aging. At the same time, traditional Pickering emulsions use small molecule inorganic nanoparticles as stabilizers, which have problems of toxicity and non-renewability, affecting the performance and environment of polyacrylate milk latex film.

Method used

An amphiphilic block copolymer grafted modified cellulose nanocrystals were used as stabilizers for Pickering emulsions to prepare a cellulose nanocrystal modified full bio-based polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

Benefits of technology

The polyacrylate composite emulsion is realized in green and environmentally friendly, with good hydrophobicity, antibacteriality and ultraviolet resistance, avoiding the adverse effects of traditional stabilizers on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899566A_ABST
    Figure CN119899566A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cellulose nanocrystal modified full-bio-based polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions, which comprises the following steps: 1, uniformly mixing a macromolecular RAFT (reversible addition-fragmentation chain transfer) reagent, a vinyl monomer, an initiator and an organic solvent, heating in argon to obtain a product A, adding the product A into n-hexane, separating out a precipitate, and drying to obtain a product B; an amphiphilic block copolymer is obtained; mixing the amphiphilic block copolymer, the cellulose nanocrystal, N, N-dimethylformamide and a catalyst, heating, carrying out centrifugal separation to obtain a crude product B, washing and drying to obtain the amphiphilic block copolymer modified cellulose nanocrystal; 2, uniformly mixing the amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers, and carrying out ultrasonic emulsification, so as to obtain a Pickering emulsion; and 3, heating the Pickering emulsion in the presence of argon, dropwise adding an initiator aqueous solution, and reacting to obtain the cellulose nanocrystal modified full-bio-based polyacrylate composite emulsion which has hydrophobicity, antibacterial property and ultraviolet resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically is a method for preparing a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions. Background Art

[0002] Natural leather has the advantages of being soft, comfortable to the touch and breathable, and has been widely used in the production of home furnishing products. However, in actual use, it also has the following disadvantages: 1) Since leather is composed of natural collagen fibers tightly woven in three-dimensional space, a large number of microporous structures are very suitable for the growth and reproduction of microorganisms such as bacteria and fungi, which seriously threatens human health; 2) Collagen contains a large number of amino, carboxyl and hydroxyl groups, which make leather have a strong affinity for water, causing the leather surface to harden and even crack, seriously reducing the comfort and service life of leather products; 3) Ultraviolet rays can destroy the molecular structure of collagen, causing the molecules of the leather material to break or cross-link, thereby accelerating the aging process of the leather. Therefore, it is usually necessary to apply a coating material on the leather surface to form a protective film to improve the performance of the leather.

[0003] Polyacrylate has excellent film-forming and adhesive properties and is usually applied to the leather surface in the form of Pickering emulsion. Pickering emulsion is a new type of emulsion prepared by using solid particles instead of traditional small molecule surfactants as stabilizers. Compared with traditional emulsions, it has the advantages of low or non-toxicity, low cost and no pollution. It has been widely used in composite materials with special structures and functions. However, the solid particles currently used as Pickering emulsion stabilizers are mostly small molecule inorganic nanoparticles. Inorganic nanoparticles have the disadvantages of toxicity, non-renewability, poor biocompatibility and non-renewability, resulting in unsatisfactory performance of polyacrylate latex films and being unfavorable to the environment.

[0004] With the improvement of living quality, people pay more and more attention to the quality of leather and pursue the functionality and green environmental protection of leather. Therefore, it is necessary to develop a new type of polyacrylate composite emulsion to give leather products good hydrophobicity, antibacterial and anti-ultraviolet functions. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions, thereby preparing a green and environmentally friendly polyacrylate composite emulsion with excellent hydrophobicity, antibacterial and anti-ultraviolet properties.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The preparation method of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions comprises the following steps:

[0008] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0009] Step 1.1, according to the mass ratio of (10-45): (150-180): (3-5): (1600-6800), a macromolecular RAFT agent, a vinyl monomer, an initiator I and an organic solvent are added into a three-necked flask with a condenser reflux tube and a gas guide tube, argon gas is introduced into the three-necked flask, heated to 70-90° C., stirred for 7-9 hours to obtain product A, product A is added into a beaker filled with n-hexane and stirred, after precipitation, the precipitate is separated, and vacuum dried to obtain an amphiphilic block copolymer;

[0010] Step 1.2, according to the mass ratio of (9-30): (3-10): (300-1000): (1-2), add the amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and the catalyst into a three-necked flask with a condenser reflux tube, stir for 20-30 hours in an oil bath at 45-55° C., centrifuge to separate the crude product B, then wash the crude product B with tetrahydrofuran to remove the residual organic solvent, and then vacuum dry to obtain the amphiphilic block copolymer modified cellulose nanocrystals;

[0011] Step 2: Preparation of Pickering emulsion

[0012] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers are uniformly mixed in a mass ratio of (1-3): (500-1000): (80-180), and ultrasonically emulsified at room temperature to obtain a Pickering emulsion;

[0013] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0014] Step 3.1, taking initiator II according to 0.6% to 1.5% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare an initiator II aqueous solution with a mass fraction of 16.7% to 25%;

[0015] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, stir and heat to 75-85°C under argon protection, then add the initiator II aqueous solution dropwise into the three-necked flask, after the addition of the initiator II aqueous solution is completed, keep warm for 90-120 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

[0016] Furthermore, the structural formula of the macromolecular RAFT agent in step 1.1 is as follows:

[0017]

[0018] In the formula, R is isobutyric acid or isovaleric acid; Z is C12 alkylthio or C11 alkylthio; R 1 -H or -CH 3 ; R 2 -H or -CH 3 ; m and n both represent the average degree of polymerization of glycidyl acrylic acid or glycidyl methacrylate, and m=15-100, n=15-100.

[0019] Furthermore, the initiator I in step 1.1 is at least one of azobisisobutyronitrile, azobisisovaleronitrile and azobisisoheptanenitrile.

[0020] Furthermore, the organic solvent in step 1.1 is n-hexane, 1,4-dioxane or N,N-dimethylformamide.

[0021] Furthermore, the catalyst in step 1.2 is p-toluenesulfonic acid, triethylamine or pyridine.

[0022] Furthermore, the vacuum drying temperature in step 1.1 and step 1.2 is 40°C.

[0023] Furthermore, the vinyl monomer in step 1.1 and step 2 is at least one of isobornyl acrylate, methyl vanillin acrylate, vanillin acrylate, lauryl acrylate, tetrahydrofurfuryl acrylate, lauryl methacrylate and tetrahydrofurfuryl methacrylate.

[0024] Furthermore, the ultrasonic emulsification in step 2 is performed using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 8% to 25% for 5 to 30 minutes.

[0025] Furthermore, the initiator II in step 3.1 is ammonium persulfate, potassium persulfate or sodium persulfate.

[0026] Furthermore, in step 3.2, the time for adding the aqueous solution of initiator II to the three-necked flask is 60 to 120 minutes.

[0027] Compared with the prior art, the present invention has the following technical effects:

[0028] The present invention takes into account that cellulose nanocrystals CNC are abundant natural organic nanomaterials with the characteristics of low density, high aspect ratio, high crystallinity and low cost, etc., and uses amphiphilic block copolymers to graft and modify cellulose nanocrystals to obtain modified cellulose nanocrystals with good wettability and dispersibility. The modified cellulose nanocrystals are used as stabilizers for Pickering emulsions to obtain cellulose nanocrystal-modified bio-based polyacrylate composite emulsions with good hydrophobicity, antibacterial properties and UV resistance, thereby avoiding the adverse effects of traditional small molecule surfactants on the performance and environment of polyacrylate latex films and broadening the application range of polyacrylate emulsions.

[0029] The vinyl monomers selected in the present invention are all bio-based monomers, which inherit the characteristics of lignin, such as aromatic ring structure and rich in various active oxygen-containing functional groups (hydroxyl groups, aldehyde groups); at the same time, they overcome the problems of uneven structural composition and poor designability of cross-linked network macromolecular state that need to be faced when lignin is directly applied; therefore, the modification of polyacrylates by vinyl monomers can not only improve the hydrophobicity, antibacterial and anti-ultraviolet properties of polyacrylates, but also reduce the use of petroleum-based materials in the synthesis process, adhere to the scientific concept of green environmental protection, and make the synthetic materials have good degradation and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : FT-IR spectrum of the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 of the present invention;

[0031] Figure 2 : Photograph of the water contact angle of the latex film formed by the cellulose nanocrystal-modified all-biobased polyacrylate composite latex prepared in Example 1 of the present invention;

[0032] Figure 3 : Photograph of ultraviolet shielding performance of latex film formed by cellulose nanocrystal-modified all-biobased polyacrylate composite latex prepared in Example 1 of the present invention;

[0033] Figure 4 : Photo of the antibacterial performance of the latex film formed by the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0035] The macromolecular RAFT agent selected in Examples 1 to 5 was synthesized with reference to CHSuch, E.Rizzardo, AKSerelis, BSHawkett, RGGilbert, CJFerguson, RJHughes, E.Olejnik, Aqueous dispersions of polymer particles.2006, and its structural formula is as follows:

[0036]

[0037] In the formula, R is isobutyric acid or isovaleric acid; Z is C12 alkylthio or C11 alkylthio; R 1 -H or -CH 3 ; R 2 -H or -CH 3 ; m and n both represent the average degree of polymerization of glycidyl acrylic acid or glycidyl methacrylate, and m=15-100, n=15-100.

[0038] Example 1

[0039] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0040] Step 1.1, according to the mass ratio of 10:150:3:1600, a macromolecular RAFT agent, a vinyl monomer, azobisisobutyronitrile and 1,4-dioxane are added to a three-necked flask with a condenser reflux tube and an air guide tube, and argon is introduced into the three-necked flask for 20 minutes, and then heated to 70°C, and mechanically stirred at a speed of 200 rpm for 9 hours to obtain product A, and product A is added to a beaker filled with n-hexane and stirred. After precipitation, the precipitate is separated, and then the precipitate is added to another beaker filled with n-hexane. Repeat twice to remove the residual organic solvent, and vacuum dry at 40°C to obtain an amphiphilic block copolymer, wherein: the vinyl monomer is a mixture of lauryl methacrylate and methyl vanillin acrylate in a mass ratio of 1:2;

[0041] Step 1.2, taking an amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and triethylamine in a mass ratio of 9:3:300:1, adding them into a three-necked flask with a condenser reflux tube, stirring at a speed of 300 rpm / min for 20 hours under an oil bath condition of 45°C, centrifuging to separate a crude product B, washing the crude product B three times with tetrahydrofuran, and vacuum drying at 40°C to obtain an amphiphilic block copolymer-modified cellulose nanocrystal;

[0042] Step 2: Preparation of Pickering emulsion

[0043] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers were uniformly mixed in a mass ratio of 1:500:80, and ultrasonic emulsification was performed for 5 minutes at room temperature using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 25% to obtain a Pickering emulsion, wherein the vinyl monomer was prepared by mixing lauryl methacrylate and methyl vanillin acrylate in a mass ratio of 4:1;

[0044] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0045] Step 3.1, taking ammonium sulfate according to 1.1% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare an ammonium sulfate aqueous solution with a mass fraction of 16.7%;

[0046] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, and while stirring at a speed of 220 r / min, introduce argon gas into the three-necked flask for 10 minutes, heat to 75°C, and add ammonium sulfate aqueous solution to the three-necked flask, and the ammonium sulfate aqueous solution is added dropwise within 60 minutes. After the addition of the ammonium sulfate aqueous solution is completed, keep warm for 90 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

[0047] from Figure 1 It can be seen that 2921cm -1 and 2855cm -1 The peak at is attributed to -CH 3 With -CH 2 -Stretching vibration absorption, 1721cm -1 The peak at 1593 cm is attributed to the stretching vibration absorption peak of -C=O in ester compounds and -C=O in VMA. -1 and 1461cm -1 The absorption peak at 1262 cm is attributed to the stretching vibration of C=C in the VMA benzene ring skeleton. -1 and 1117cm -1 The peak at belongs to the stretching vibration of the ester group COC, indicating that Example 1 successfully prepared a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion.

[0048] The cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 was placed in a silicone mold, molded at room temperature for 48 hours, placed in an oven at 80°C for drying to remove residual moisture, and then annealed at 120°C for 30 minutes to obtain a latex film, which was used to test the hydrophobicity, antibacterial and anti-ultraviolet functions, respectively. The results are as follows: Figure 2 to Figure 4As shown, where:

[0049] See also Figure 2 , it can be seen that the water contact angle of the latex film is 125.8°, indicating that the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 has good hydrophobicity;

[0050] See also Figure 3 In the first picture from the left, take a piece of latex film and place it on the test area of ​​the UV sensor card, then see Figure 3 In the second picture from the left, the UV sensor card with latex film is placed under a 365nm UV light source. Finally, the UV light source is turned off and the latex film is removed. The results are as follows Figure 3 As shown in the third picture from the left, it can be seen that the area of ​​the UV sensor card covered by the latex film is white, and the area not covered by the latex film is purple, indicating that the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 has good anti-ultraviolet function;

[0051] Take a piece of latex film and put it in the Staphylococcus aureus liquid as the test group, and take the Staphylococcus aureus liquid without latex film as the control group. After 24 hours, observe the changes in the number of Staphylococcus aureus in the test group and the control group. Figure 4 It can be seen that the number of Staphylococcus aureus in the test group is significantly less than that in the control group, indicating that the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion prepared in Example 1 can inhibit the growth of Staphylococcus aureus and has good antibacterial properties.

[0052] Example 2

[0053] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0054] Step 1.1, according to the mass ratio of 15:160:4:3000, a macromolecular RAFT agent, a vinyl monomer, azobisisoheptanenitrile and N,N-dimethylformamide are added into a three-necked flask with a condenser reflux tube and a gas guide tube, argon is introduced into the three-necked flask for 25 minutes, heated to 80°C, and mechanically stirred at a speed of 300 rpm for 7 hours to obtain product A, and product A is added to a beaker filled with n-hexane and stirred. After precipitation, the precipitate is separated and added to another beaker filled with n-hexane, and the process is repeated 3 times to remove the residual organic solvent, and vacuum dried at 40°C to obtain an amphiphilic block copolymer, wherein: the vinyl monomer is a mixture of lauryl methacrylate and vanillin acrylate in a mass ratio of 1:1;

[0055] Step 1.2, taking an amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and pyridine in a mass ratio of 14:5:450:1.5, adding them into a three-necked flask with a condenser reflux tube, stirring at a speed of 200 rpm / min for 30 hours under an oil bath condition of 50°C, centrifuging to separate a crude product B, washing the crude product B twice with tetrahydrofuran, and vacuum drying at 40°C to obtain an amphiphilic block copolymer-modified cellulose nanocrystal;

[0056] Step 2: Preparation of Pickering emulsion

[0057] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers were uniformly mixed in a mass ratio of 2:600:100, and ultrasonic emulsification was performed for 10 minutes at room temperature using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 20% to obtain a Pickering emulsion, wherein the vinyl monomer was a mixture of lauryl methacrylate and vanillin acrylate in a mass ratio of 35:13;

[0058] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0059] Step 3.1, taking ammonium sulfate according to 1.1% of the mass of the vinyl monomer in step 2, adding it to deionized water to prepare an ammonium sulfate aqueous solution with a mass fraction of 18%;

[0060] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, and while stirring at a speed of 250 r / min, introduce argon gas into the three-necked flask for 15 minutes, heat to 85°C, and add ammonium sulfate aqueous solution to the three-necked flask, and the ammonium sulfate aqueous solution must be added within 90 minutes. After the addition of the ammonium sulfate aqueous solution is completed, keep warm for 100 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

[0061] Example 3

[0062] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0063] Step 1.1, according to the mass ratio of 45:180:5:6800, a macromolecular RAFT agent, a vinyl monomer, azobisisoheptanenitrile and 1,4-dioxane are added to a three-necked flask with a condenser reflux tube and a gas guide tube, argon is introduced into the three-necked flask for 30 minutes, heated to 70°C, and mechanically stirred at a speed of 200 rpm for 9 hours to obtain product A, and product A is added to a beaker filled with n-hexane and stirred, and the precipitate is separated and added to another beaker filled with n-hexane, and the precipitate is repeated 3 times to remove the residual organic solvent, and vacuum dried at 40°C to obtain an amphiphilic block copolymer, wherein: the vinyl monomer is a mixture of isobornyl acrylate and methyl vanillin acrylate in a mass ratio of 2:5;

[0064] Step 1.2, adding the amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and triethylamine in a mass ratio of 30:10:1000:2 into a three-necked flask with a condenser reflux tube, stirring at 200 rpm for 30 h in an oil bath at 50°C, centrifuging to separate the crude product B, washing the crude product B twice with tetrahydrofuran, and vacuum drying at 40°C to obtain the amphiphilic block copolymer modified cellulose nanocrystals;

[0065] Step 2: Preparation of Pickering emulsion

[0066] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers were uniformly mixed in a mass ratio of 3:1000:180, and ultrasonic emulsification was performed for 30 minutes at room temperature using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 8% to obtain a Pickering emulsion, wherein the vinyl monomers were prepared by mixing isobornyl acrylate, lauryl acrylate and tetrahydrofurfuryl acrylate in a mass ratio of 1:2:1;

[0067] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0068] Step 3.1, taking potassium persulfate according to 1.5% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare a potassium persulfate aqueous solution with a mass fraction of 25%;

[0069] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, and while stirring at a speed of 150 r / min, introduce argon into the three-necked flask for 20 minutes, heat to 80°C, and add potassium persulfate aqueous solution to the three-necked flask, and the potassium persulfate aqueous solution must be added within 120 minutes. After the potassium persulfate aqueous solution is added, keep warm for 120 minutes, and cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

[0070] Example 4

[0071] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0072] Step 1.1, according to the mass ratio of 28:165:3:4200, a macromolecular RAFT agent, a vinyl monomer, azobisisovaleronitrile and n-hexane are added into a three-necked flask with a condenser reflux tube and an air guide tube, and argon is introduced into the three-necked flask for 20 minutes, and then heated to 80°C, and mechanically stirred at a speed of 200 rpm for 8 hours to obtain product A, and product A is added to a beaker filled with n-hexane and stirred. After precipitation, the precipitate is separated, and then the precipitate is added to another beaker filled with n-hexane. Repeat 3 times to remove residual organic solvent, and vacuum dry at 40°C to obtain an amphiphilic block copolymer, wherein: the vinyl monomer is a mixture of lauryl acrylate, tetrahydrofurfuryl acrylate and tetrahydrofurfuryl methacrylate in a mass ratio of 1:1:1;

[0073] Step 1.2, taking an amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and p-toluenesulfonic acid in a mass ratio of 20:6.5:650:1, adding them into a three-necked flask with a condenser reflux tube, stirring at a speed of 300 rpm / min for 20 hours under an oil bath condition of 55°C, centrifuging to separate a crude product B, washing the crude product B three times with tetrahydrofuran, and vacuum drying at 40°C to obtain an amphiphilic block copolymer-modified cellulose nanocrystal;

[0074] Step 2: Preparation of Pickering emulsion

[0075] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers are uniformly mixed in a mass ratio of 1.5:750:145, and ultrasonic emulsification is performed for 20 minutes at room temperature using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 10% to obtain a Pickering emulsion, wherein the vinyl monomer is a mixture of tetrahydrofurfuryl acrylate and tetrahydrofurfuryl methacrylate in a mass ratio of 3:1;

[0076] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0077] Step 3.1, taking potassium persulfate according to 1.3% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare a potassium persulfate aqueous solution with a mass fraction of 23%;

[0078] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, and while stirring at a speed of 220 r / min, introduce argon gas into the three-necked flask for 10 minutes, heat to 75°C, and add potassium persulfate aqueous solution to the three-necked flask, and the potassium persulfate aqueous solution is added dropwise within 70 minutes. After the potassium persulfate aqueous solution is added dropwise, keep warm for 110 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

[0079] Example 5

[0080] Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals

[0081] Step 1.1, according to the mass ratio of 36:170:5:5500, a macromolecular RAFT agent, a vinyl monomer, azobisisobutyronitrile and 1,4-dioxane are added to a three-necked flask with a condenser reflux tube and a gas guide tube, and argon gas is introduced into the three-necked flask for 20 minutes, and then heated to 90°C, and mechanically stirred at a speed of 250 rpm for 7 hours to obtain product A, and product A is added to a beaker filled with n-hexane and stirred. After precipitation, the precipitate is separated, and then the precipitate is added to another beaker filled with n-hexane. Repeat 4 times to remove the residual organic solvent, and vacuum dry at 40°C to obtain an amphiphilic block copolymer, wherein: the vinyl monomer is isobornyl acrylate;

[0082] Step 1.2, taking an amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and triethylamine in a mass ratio of 25:8:800:2, adding them into a three-necked flask with a condenser reflux tube, stirring at a speed of 250 rpm / min for 25 hours under an oil bath condition of 45°C, centrifuging to separate a crude product B, washing the crude product B three times with tetrahydrofuran, and vacuum drying at 40°C to obtain an amphiphilic block copolymer-modified cellulose nanocrystal;

[0083] Step 2: Preparation of Pickering emulsion

[0084] The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers were uniformly mixed in a mass ratio of 2.5:900:160, and ultrasonic emulsification was performed for 8 minutes at room temperature using an ultrasonic pulverizer with a total power of 1500 W and an ultrasonic power of 15% to obtain a Pickering emulsion, wherein the vinyl monomer was vanillin acrylate;

[0085] Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions

[0086] Step 3.1, taking sodium persulfate according to 0.6% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare a sodium persulfate aqueous solution with a mass fraction of 20%;

[0087] Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, and while stirring at a speed of 180 r / min, introduce argon into the three-necked flask for 10 minutes, heat to 85°C, and add sodium persulfate aqueous solution to the three-necked flask, and the sodium persulfate aqueous solution is added dropwise within 100 minutes. After the sodium persulfate aqueous solution is added dropwise, keep warm for 100 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

Claims

1. A method for preparing a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions, characterized in that: The steps include: Step 1: Preparation of amphiphilic block copolymer modified cellulose nanocrystals Step 1.1, according to the mass ratio of (10-45): (150-180): (3-5): (1600-6800), a macromolecular RAFT agent, a vinyl monomer, an initiator I and an organic solvent are added into a three-necked flask with a condenser reflux tube and a gas guide tube, argon gas is introduced into the three-necked flask, heated to 70-90° C., stirred for 7-9 hours to obtain product A, product A is added into a beaker filled with n-hexane and stirred, after precipitation, the precipitate is separated, and vacuum dried to obtain an amphiphilic block copolymer; Step 1.2, according to the mass ratio of (9-30): (3-10): (300-1000): (1-2), add the amphiphilic block copolymer, cellulose nanocrystals, N,N-dimethylformamide and the catalyst into a three-necked flask with a condenser reflux tube, stir for 20-30 hours in an oil bath at 45-55° C., centrifuge to separate the crude product B, then wash the crude product B with tetrahydrofuran to remove the residual organic solvent, and then vacuum dry to obtain the amphiphilic block copolymer modified cellulose nanocrystals; Step 2: Preparation of Pickering emulsion The amphiphilic block copolymer modified cellulose nanocrystals, deionized water and vinyl monomers are uniformly mixed in a mass ratio of (1-3): (500-1000): (80-180), and ultrasonically emulsified at room temperature to obtain a Pickering emulsion; Step 3: Preparation of a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions Step 3.1, taking initiator II according to 0.6% to 1.5% of the mass of the vinyl monomer in step 2, adding it into deionized water to prepare an initiator II aqueous solution with a mass fraction of 16.7% to 25%; Step 3.2, transfer the Pickering emulsion to a three-necked flask with a condenser reflux tube and an air duct, stir and heat to 75-85°C under argon protection, then add the initiator II aqueous solution dropwise into the three-necked flask, after the addition of the initiator II aqueous solution is completed, keep warm for 90-120 minutes, and then cool to room temperature to obtain a cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion with hydrophobic, antibacterial and anti-ultraviolet functions.

2. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The structural formula of the macromolecular RAFT agent in step 1.1 is as follows: In the formula, R is isobutyrate or isovalerate; Z is C12 alkylthio or C11 alkylthio; R1 is -H or -CH3; R2 is -H or -CH3; m and n both represent the average degree of polymerization of glycidyl acrylic acid or methacrylate, and m=15-100, n=15-100.

3. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The initiator I in step 1.1 is at least one of azobisisobutyronitrile, azobisisovaleronitrile and azobisisoheptanenitrile.

4. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The organic solvent in step 1.1 is n-hexane, 1,4-dioxane or N,N-dimethylformamide.

5. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The catalyst in step 1.2 is p-toluenesulfonic acid, triethylamine or pyridine.

6. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The vacuum drying temperature in step 1.1 and step 1.2 is 40°C.

7. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The vinyl monomers in step 1.1 and step 2 are at least one of isobornyl acrylate, methyl vanillin acrylate, vanillin acrylate, lauryl acrylate, tetrahydrofurfuryl acrylate, lauryl methacrylate and tetrahydrofurfuryl methacrylate.

8. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The ultrasonic emulsification in step 2 is performed using an ultrasonic pulverizer with a total power of 1500W and an ultrasonic power of 8% to 25% for 5 to 30 minutes.

9. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: The initiator II in step 3.1 is ammonium persulfate, potassium persulfate or sodium persulfate.

10. The method for preparing the cellulose nanocrystal-modified all-biobased polyacrylate composite emulsion having hydrophobic, antibacterial and anti-ultraviolet functions according to claim 1, characterized in that: In the step 3.2, the time for adding the aqueous solution of initiator II to the three-necked flask is 60 to 120 minutes.

Citation Information

Patent Citations

  • Preparation method for nano-crystalline cellulose / fluorine containing polyacrylate compound emulsion

    CN106749860A

  • Method for modifying cellulose nanocrystals by using photoresponsive fluorine-containing amphiphilic block copolymer

    CN110938211A

  • Preparation method of dual self-repairing cellulose nanocrystal / fluorine-containing polyacrylate composite emulsion

    CN114133591A

  • Bio-based block polymers derived from lignin and fatty acids

    US20140275435A1